The Urgency of Islamic Moderation in Aspects Dakwah and Sara Cross Communication - Dahlan Lama Bawa; Amirah Amirah; Muktashim Billah; Muhammad Yasin (Journal on Education, 2024)
Research on the Urgency of Islamic Moderation in the Aspect of Da'wah and Communication Between SARA, motivated by the escalation of inter-religious conflicts in Indonesia after the 1998 reform, such as in Ambon, Poso, Situbondo and Sambas. This study aims to determine the Theological Basis of Moderation, the Urgency of Ethnicity, Religion and Race (SARA) Da'wah and the Urgency of Cross-SARA Communication. Knowledge of these three aspects is very important as an effort to prevent conflict, because the conflict is like a malignant cancer that at any time inflames and damages one's own resilience joints. Kind This research is included in the category of library research The results of the research obtained include, 1) The Theological Basis of Islamic Moderation is explained in Surah Al-Baqarah verse 143 (wa kadzalika ja'alanakum ummatan wasathan) which is used as a theological basis or starting point for religious moderation. There are three main keys in the application of wasathiyyah, namely correct knowledge, controlled emotions and vigilance. 2) The urgency of Ethnicity, Religion and Race (SARA) Da'wah is to care for a tolerant religious character, to strive for universal peace in the midst of differences in Ethnicity/Nation, Religion and Race/Group. Da’wah Suku, Agama dan Ras (SARA) is a da'wah that reconciles, enlightens and edifies. 3) Poor communication will cause miscommunication even the worst can be a trigger for conflict, while conflict is like a malignant cancer that at any time can damage the body's immune system and nervous tissue, so you must always maintain and maintain the body's immunity to stay healthy. Herein lies the importance or urgency of cross-SARA communication to prevent miscommunication and discommunication that has the potential to trigger conflict in Indonesia.